New and little-known species of Empis (Diptera: Empididae) from Bulgaria, Israel and Turkey, with keys to the Palaearctic Pachymeria and the Mediterranean Xanthempis - Shamshev, Igor V.; Barták, Miroslav (Zootaxa, 2019)
Empis (Pachymeria) vikhrevi sp. nov. is described from Bulgaria and Turkey (Bolu Province). Empis (Xanthempis) adanaensis sp. nov. is described from Turkey (Adana Province). The subgenus Xanthempis is registered for the first time from Israel, with one species E. (X.) testiculata Bezzi, 1909. Also, this species is recorded for the first time from Turkey (Muğla Province) and the female is described for the first time. A subdivision of Pachymeria into two species groups (E. femorata group and E. tumida group) is proposed. Keys to species of Pachymeria known from the Palaearctic and Xanthempis known from the Mediterranean basin are presented.